Infectious Wildlife Diseases in Austria—A Literature Review From 1980 Until 2017 - Trimmel, Nina Eva; Walzer, Chris (Frontiers in Veterinary Science, 2020)
This literature review examines infectious wildlife disease research in Austria. We analysed 226 research papers, published between 1980 and 2017. We determined that wildlife disease papers increased significantly from 0.8 ± 0.8 publications per year in the first decade (1980−1989) when compared to 2008−2017 with an average of 12.9 ± 4.1 publications per year. We illustrate information about the most investigated diseases and highlight the lack of research into certain wildlife pathogens. A special emphasis was given to diseases with zoonotic potential. The review showed that research focused on a few select species like the red fox (Vulpes vulpes), red deer (Cervus elaphus) and wild boar (Sus scrofa), all game species. Moreover, diseases affecting livestock and human health were seen more often. The review also found that only a low number of publications actually stated disease prevalence and confidence interval data. The reported diseases identified, were classified according to their notifiable status and the distribution at the wildlife-human and wildlife-livestock interface. Furthermore, we try to argue why research into some diseases is prioritized, and why other diseases are underrepresented in current Austrian research. While spatio-temporal indicators could not be assessed due to the variability in methodologies and objectives of various studies, the information provided by this review offers the first comprehensive evaluation of the status of infectious wildlife disease research in Austria. Therefore this study could assist investigators to identify further areas of priorities for research and conservation efforts and for wildlife management professionals to inform policy and funding strategies. With this review, we want to encourage research in the field of wildlife diseases in Austria to enhance current knowledge in the prevention of further loss in biodiversity and to find new measures to promote "One Health" on a global scale.